Bank Reactions to COVID-19 Pandemic and Currency Crisis: Empirical Evidence from Iran - Reza Gholami; Aisyah Abdul-Rahman (International Journal of Islamic Economics and Finance (IJIEF), 2022)
Since 2019, the global economy is suffering from a crisis caused by a novel virus called Covid-19 which create uncertainty condition for investors by affecting both supply and demand side of the economy, simultaneously. It is expected that investors be more cautious in investing under uncertain condition created by Covid-19, but this issue has been neglected in the literature. We address it by examining the banks’ behavior in constructing their portfolio based on empirical evidence from the Islamic Republic of Iran (Iran). We focus on banking system as it is a major investor in the economy that is more sensitive to any surprises due to the structure of its business model. By categorizing the Iranian banks’ assets into fixed, variable, and no-interest rate, we examine the weight change of the three contracts in the banks’ portfolio during the Covid-19 and a regular currency crisis. We apply ARDL regression analysis for monthly data (January 2010 to June 2021) from Iranian Central Bank. The results revealed that the weight of the fixed rate contracts in the banks’ portfolio, on average, is higher during crisis compared to normal periods, and is even higher facing Covid-19 or uncertainty condition. This study adds to the literature of Covid-19 crisis and its findings help policymakers to provide a prompt reply of such crisis through banking system.